URGENSI PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA menurut Undang-undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga - Purbadiri, Anies Marsudiati (IAIN Pekalongan, 2011)
Violence against women impede or negate the possibility of women to enjoy human rights and freedom are incompatible with the Constitution and Law no. 23 Year 2004 on the Elimination of Domestic Violence (PKDRT). According to Law no. 23 In 2004, the urgency of the legal protection of women are advocates for abused women with female victims of domestic violence pengananan from various parties in accordance with their areas of expertise and their respective disciplines, in this case the disciplines of law, medical and psychology